Histogenous Hypoxia and Acid Retention in Schizophrenia: Changes in Venous Blood Gas Analysis and SOD in Acute and Stable Schizophrenia Patients - Huang, Xingbing; Lu, Qiu-Ling; Zhu, Xiu-Mei; Zeng, Yi-Bin; Liu, Yun; Hu, Hao-Ying (Frontiers in Psychiatry, 2021)
Background：Oxidative stress may play an important role in the pathogenesis of schizophrenia, and there is considerable indirect evidence that hypoxia is closely related to schizophrenia, but direct evidence of hypoxia in SCH has never been found. Methods: In this study, SOD, venous blood gas and PANSS scale were examined in 40 SCH patients and compared with those of 40 healthy controls. The patients were treated with combination of atypical antipsychotics and Ditan Huayu Lishen Decoction(a Chinese medicine decoction) and examined in acute and stable period respectively. Comparison of indicators between two groups were performed using an independent samples t test，comparison of indicators between acute and stable period in SCH group was performed using paired-samples t test. Pearson’s correlation and multiple linear regression analyses were performed to investigate the relationships between the effect indicators. Results: It was found higher venous pH, PvO2 and FBG levels and lower SOD, lactic acid, and PvCO2 levels in SCH patients compared with the control group, SOD was negatively correlated with the general psychopathology subscale score(PANSS-G), and PvO2 levels was closely related to venous pH in SCH and related to PvCO2 in control group. It was also found SOD activity showed no significant difference in acute and stable period, while PvO2 showed a downward trend and venous pH was decreased significantly after treatment. Both the venous pH and PvO2 were higher in patients with SCH than that in healthy controls. Conclusion: It suggests that histogenous hypoxia and acid retention exist in relation to SCH. and there is an improvement of acid retention and a downward trend in histogenous hypoxia after combination treatment. Venous pH, PvO2 and PvCO2 are trait variables, but not state variables of SCH. The theory of histogenous hypoxia and acid retention can well explain the decrease of pH value and the increase of lactic acid in brain tissue of patients with SCH. Histogenous hypoxia and acid retention are closely related to glucose metabolism. So they may play an important role in pathophysiology for SCH.